2018
DOI: 10.18176/jiaci.0283
|View full text |Cite
|
Sign up to set email alerts
|

Persistent B Lymphocyte Depletion After an Ultralow Dose of Rituximab for Pemphigus Vulgaris

Abstract: Pemphigus vulgaris is an autoimmune bullous disease affecting the skin and mucosa. It is caused by autoantibodies targeting the adhesion molecules desmoglein 1 and desmoglein 3, which, respectively, mediate adhesion between keratinocytes in skin and mucosa, resulting in the formation of blisters and erosions. Early recognition and treatment are crucial for remission of this disorder. Treatment for severe pemphigus traditionally includes long-term corticosteroids and immunosuppressants [1]. Rituximab, a chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the other hand, high dose regimens should be preferred instead of low-dose regimens, due to longer disease response (163). Nowadays, one study recently reported on a pemphigus patient achieving successful disease remission with an ultra-low dose of RTX (200 mg in a single infusion), with persistent B-cell depletion after 6-month follow-up (172, 173). This highlights the need of further investigating individual factors that may influence RTX efficacy in an effort to personalize treatment schedules and optimize the safety.…”
Section: Treatmentmentioning
confidence: 99%
“…On the other hand, high dose regimens should be preferred instead of low-dose regimens, due to longer disease response (163). Nowadays, one study recently reported on a pemphigus patient achieving successful disease remission with an ultra-low dose of RTX (200 mg in a single infusion), with persistent B-cell depletion after 6-month follow-up (172, 173). This highlights the need of further investigating individual factors that may influence RTX efficacy in an effort to personalize treatment schedules and optimize the safety.…”
Section: Treatmentmentioning
confidence: 99%
“…Initially the most used regimen was the lymphoma protocol (375 mg/week for 4 weeks), nowadays some centres prefer two doses of 1000 mg given 2 weeks apart or 500 mg at 2 weeks interval because of the better side effect profile 10. In our experience, we observed the persistent suppression of B cell count for several months after a single very low dose of rituximab (200 mg) 11. Moreover, a recent study demonstrated that less than 1% of the conventional rituximab dose induced a nearly complete depletion of circulating B lymphocytes in healthy volunteers 12 13…”
Section: Discussionmentioning
confidence: 60%